Reverse roll-coating flow: a computational investigation towards high-speed defect free coating - Michael Webster (Mechanics of Time-Dependent Materials, 2013)
A finite element Taylor–Galerkin pressure-correction algorithm is employed to simulate a high-speed defect-free roll-coating flow, which substantiates a coating process with a free meniscus surface. Findings are applicable across a wide range of coating sectors in optimisation of coating performance, which targets adaptive and intelligent process control. Industrially, there is a major drive towards using new material products and raising coating line-speeds, to address increased efficiency and productivity. This study has sought to attack these issues by developing an effective predictive toolset for high-speed defect-free coatings. Here, time-stepping/finite element methods are deployed to model this free-surface problem that involves the transfer of a coating fluid from a roller to a substrate (of prescribed wet-film thickness). This procedure is used in conjunction with a set of constitutive equations capable of describing the relevant fluid-film rheology in appropriate detail. Quantities of pressure, lift and drag have been calculated streamwise across the flow domain, and streamline patterns reveal a large recirculating vortex around the meniscus region. Such pressure distributions across the domain display a positive peak which decreases as nip-gap size increases. Further analysis has been conducted, mimicking the presence of a wetting line, whilst varying boundary conditions at the nip. Observation has shown that such inclusion would serve as a relief mechanism to the positive peak pressures generated around the nip zone. Here, through an elasto-hydrodynamic formulation, the elastic deformation of a rubber roll cover (elastomer) has also been introduced, which offers fresh insight into the process with respect to nip-flow behaviour, and allows for the analysis of both positive and negative nip-gaps.